Financial Performance Analysis Using The Profitability Ratio at PT. Bank Rakyat Indonesia (Persero) Tbk Period 2020-2022 - Djilhamzah, Alief Salsabila; Ramli, Anwar; Dipoatmojo , Tenri S.P; Musa, Chalid Imran; Sahabuddin , Romansyah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
This study aims to determine the financial performance of PT. Bank BRI (Persero) Tbk during the 2020-2022 period. The research method used is quantitative with data collection techniques through documentation and observation, which involves financial statement data such as balance sheets and profit and loss statements prepared by Bank BRI. The data analysis technique involves the use of profitability financial ratio analysis consisting of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The research findings show that Return on Assets and Return on Equity are experiencing very healthy conditions, while the Net Profit Margin value shows unhealthy conditions in the performance of PT. Bank BRI (Persero)